2016
DOI: 10.1038/jhh.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Detecting non-adherence by urine analysis in patients with uncontrolled hypertension: rates, reasons and reactions

Abstract: Poor adherence with pharmacotherapy is well recognised as one of the main barriers to achieving satisfactory blood pressure control, although accurately measuring patient adherence has historically been very challenging. Urine analysis by high-performance liquid chromatography-tandem mass spectrometry has recently become routinely available as a method of screening for non-adherence. In addition to measuring rates of adherence in hypertensive patients, this study aimed to investigate the reasons for non-adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…This form of nonintentional nonadherence to antihypertensive therapy was also demonstrated as one of the main barriers to adherence in other studies. 41 , 42 Our study is not immune from the so-called toothbrush effect 43 —patients may have taken their medications just before their clinic appointment and thus influence their clinic BP measurement. To this end, the availability of 24-hour ambulatory BP monitoring data showing the same direction of BP changes is reassuring because this investigation was conducted at a different time point from the clinic appointment.…”
Section: Discussionmentioning
confidence: 96%
“…This form of nonintentional nonadherence to antihypertensive therapy was also demonstrated as one of the main barriers to adherence in other studies. 41 , 42 Our study is not immune from the so-called toothbrush effect 43 —patients may have taken their medications just before their clinic appointment and thus influence their clinic BP measurement. To this end, the availability of 24-hour ambulatory BP monitoring data showing the same direction of BP changes is reassuring because this investigation was conducted at a different time point from the clinic appointment.…”
Section: Discussionmentioning
confidence: 96%
“…Studies in this setting using high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS) of random urine samples have shown that up to half of patients were totally or partially non-adherent to antihypertensive treatment. 26 Healthcare professionals should therefore have a high index of suspicion for non-adherence in patients with poor BP control despite being prescribed multiple antihypertensives. A non-judgemental and non-confrontational approach to the issue is recommended when discussing this with the patient, in order to avoid a breakdown in the patient-clinician relationship.…”
Section: Non-adherencementioning
confidence: 99%
“…Strategies to improve adherence should be tailored to the individual because patients have different reasons for nonadherence. Intolerance to medication is a common factor 26 and patients with multiple drug intolerance should be referred to a hypertension specialist (see Table 2).…”
Section: Non-adherencementioning
confidence: 99%
“…Third, we lacked data on the dose and adherence of RASi in this cohort of patients. The reported rates of patient RASi adherence for cardiovascular protection are high, range from 68 to 92% in the literature 35,36 . Finally, both CABG and valve surgery patients were included in this study since RASi have been shown to be beneficial in both groups of patients 1,2,610,12,18,19 .…”
Section: Discussionmentioning
confidence: 99%